Molecular Diversity of Bacterial Isolated from Cozy and Cold Spring Water in Mosul / Iraq - Mohammed Abdul_Razak Ibraheem Al-Qatan (Journal of Global Pharma Technology, 2019)
The study involved determining the phenotypic and genotypic characterizations of the bacterial isolates from cozy springing water. Three bacterial species were elite supported on morphological bacterial, physiological and biochemical tests. In addition to molecular diagnosis using 16srRNAsequences. The cells were Rod_cocci, non-motile and their colonies appeared pigment red, yellow-orange and white, the range of their growth was at ph 4-8, temperature range 10-40 and the range of growth in NaCl 2-15%. All isolates were aerobic, positive for  catalase, oxidase, nitrate redaction and negative methyl red, also produced acid from fermentation of (arabinose, fructose, maltose and trehalose), while our  isolates exhibited variable results formation of acid from sugares such as  glucose, galactose, mannose, sorbitole, lactose and sucrose). Also the isolates were resistant for the foiiowing antibiotics amoxicillin, carbencillin, erythromycin, streptomycin and tetracycline but with various resistance to gentamycin and novobiocin. The 16srRNA sequences were performed by the ABI 3130XL gene analysis in Biology Bolumu 21280_Diyarbakir/Turkey. The isolated strains were mainly Serratia nematodiphila, Staphylococcus saprophyticus and Bacillus vietnamensis. Bioinformatic analysis alignment was done by Clustal W program mega 5 and phylogenetic tree analysis was constructed and drawn by Nieghbour_ joining program.Keywords: Phylogenetic tree, Spring water, Bioinformatic.